Between desire and passion Teresa de Cartagena - Kim, Yonsoo (The medieval and early modern Iberian world, 2012)
Teresa de Cartagena's distinctive writing locates her place in a line of European women intellectuals, presenting an indispensible dialogue among her peers of the early modern age. Tracing her predecessors' achievements, we can appreciate the multifaceted characteristics of Teresa's writings.